Global Stability for SIR Models with Nonlinear Incidence and Removal Functions - Díaz Marín, H.; Osuna, O.; Villavicencio Pulido, J. G. (Trends in Computational and Applied Mathematics, 2024)
In this work, we provide some sufficient conditions to study the global asymptotic stability of the endemic equilibrium for certain models in mathematical epidemiology with nonlinear incidence and removal functions. We also present numerical examples in order to illustrate our results.